I'm here to help. Ask as many questions as you like. I'm not afraid of questions.

Basically a function is inverse of the other, if that function can be substituted into the other, and the result be simply x.

For example, say the function is f(x)=2x. and the other function is g(x)=3x-8. When you plug in either equation in place of x, if you simplify it should only be x left.

So f(g(x))=2(3x-8)

f(g(x))=6x-16

6x-16 isn't x.

These functions are not inverses of eachother.

But to the one you asked about:

f(x)=1/7x + 2/7

g(x)=7x - 2.

f(g(x))=1/7 (7x - 2) + 2/7

f(g(x))=7/7x - 2/7 + 2/7

7/7=1

-2/7+2/7=0

So when function g(x) is substituted into f(x), the remaining value is simply x. No we have to plug f(x) into g(x) to see if we just get x.

g(f(x))=7(1/7x + 2/7) -2

7/7x + 14/7 - 2

7/7= 1

14/7=2

2-2=0

Which means g(f(x))=x.

These two functions are inverses of eachother.

I know math can be difficult. I have different ways of thinking, so I had a hard time in all my math classes. Math can be difficult, but if you need help in the future, let me know. Email me: doctorturner7@gmail.com

Take care partner.

-Doctor Turner

Glad to help. If you need further clarification, let me know.
-Doctor Turner